Characteristics of VHF Line-Of-Sight Propagation for Point-To-Area Network in A Tropical Atmosphere - Igwe, K. C. (Journal of Science and Technology, 2022)
This paper investigates the degree of influence of weather and the environment on radio signal propagation between a Very High Frequency (VHF) band transmitter and a receiver in the North Central region of Nigeria. Signal strength measurements were made from a Frequency Modulation (FM) station broadcasting at 100.5 MHz using a digital signal level meter. The results obtained showed that received signal strength (RSS) values were higher during the wet season with average values ranging between 41 dBµV and 50 dBµV as compared to lower values of between 36 dBµV and 48 dBµV recorded during the dry season. The computed radio refractivity revealed similar trend of low dry season values in the range of 291 N-units to 345 N-units and high wet season values ranging between 350 N-units and 363 N-units. Also, the cumulative frequency distribution of the signal level computed showed that 50 dBµV had the highest number of samples, while 60 dBµV and 70 dBµV recorded the lowest number of samples. In addition, dry season values of attenuation deduced ranged between 1.6 dB and 2.8 dB, while average wet season attenuation values vary from 1.4 dB to 2.3 dB. Finally, the RSS was modeled using ITU-R P.526-12 to predict losses due to diffraction over the earth’s curvature, and the results obtained revealed that the model underestimated the RSS for the radio link.